An exploratory genome-wide analysis of genetic risk for alcoholic hepatitis. (2nd November 2017) - Beaudoin, James J.; Long, Nanye; Liangpunsakul, Suthat; Puri, Puneet; Kamath, Patrick S.; Shah, Vijay; Sanyal, Arun J.; Crabb, David W.; Chalasani, Naga P.; Urban, Thomas J.; ,
Abstract: Objectives: To elucidate the genetic variability between heavy drinkers with and without alcoholic hepatitis (AH). Materials and methods: An exploratory genome-wide association study (GWAS; NCT02172898) was conducted comparing 90 AH cases with 93 heavy drinking matched controls without liver disease in order to identify variants or genes associated with risk for AH. Individuals were genotyped using the multi-ethnic genotyping array, after which the data underwent conventional quality control. Using bioinformatics tools, pathways associated with AH were explored on the basis of individual variants, and based on genes with a higher 'burden' of functional variation. Results: Although no single variant reached genome-wide significance, an association signal was observed for PNPLA3 rs738409 ( p = .01, OR 1.9, 95% CI 1.1–3.1), a common single nucleotide polymorphism that has been associated with a variety of liver-related pathologies including alcoholic cirrhosis. Using the improved gene set enrichment analysis for GWAS tool, it was shown that, based on the single variants' trait-association p- values, multiple pathways were associated with risk for AH with high confidence (false discovery rate [FDR] < 0.05), including several pathways involved in lymphocyte activation and chemokine signaling, which coincides with findings from other research groups. Several Tox Functions and Canonical Pathways were highlighted using Ingenuity Pathway Analysis, with an especially conspicuous role for pathways related to ethanol degradation, which is not surprising considering the phenotype of the genotyped individuals. Conclusion: This preliminary analysis suggests a role for PNPLA3 variation and several gene sets/pathways that may influence risk for AH among heavy drinkers.